APLICAÇÃO DE MODELO NUMÉRICO QUASE-TRIDIMENSIONAL AO SISTEMA BEBERIBE-PE - Montenegro, Abelardo A. de A.; França, H. P.; Montenegro, S. M. G. L.; Gênova, D. de M.; André, H. O.; Júnior, A. R. (Águas Subterrâneas, 1992)
INDISPONÍVEL